VD_FINDINFO Jug / 2012 / 41 vom 2. Februar 2012 - VD Tribunal cantonal (2012)
LF SUR LA PRÉVOYANCE PROFESSIONNELLE VIEILLESSE, SURVIVANTS ET INVALIDITÉ, SURASSURANCE, INVALIDITÉINFIRMITÉ, INTÉRÊT MORATOIRE, RENTE D'INVALIDITÉ, REVENU DÉTERMINANT | 83 LOJV, 26 al. 1 LPP, 26 al. 2 LPP, 34a LPP, 49 al. 2 LPP, 73 al. 1 LPP, 73 al. 2 LPP, 73 al. 3 LPP, 24 al. 1 OPP2, 24 al. 2 OPP2, 24 al. 5 OPP2, 109 al. 1 LPA-VD, 55 LPA-VD, 93 al. 1 let. c LPA-VD